Authoring the "unspeakables", moralising the public sphere: A Literary examination of social commitment and the artistic vision in Sifiso Nyathi’s oeuvre - Iitula, Leena K. (IJRDO - Journal of Social Science and Humanities Research, 2021)
Abstract Literature offers a medium to speak directly about issues that society may veil because they are viewed as “unspeakable”. This study offers a much-needed critical analysis of how a Namibian writer, Sifiso Nyathi, through his oeuvre, commits to moralise the public sphere by authoring the commonly unsaid and veiled societal matters. The study employs a qualitative approach and data was analysed using content analysis. By adopting two theories; Maria Pia Lara’s illocutionary approach and the African worldview, the article reveals that Africans are highly spiritual, superstitious and their belief in ‘another presence’ is undisputable. The study reveals that there are certain issues in the Namibian society which are not openly discussed, issues which are commonly controversial or viewed as aggressive towards accepted knowledge. The study will offer renewed insight into Nyathi’s works and African literature in general. The unique approach of blending different genres of literature; plays, poetry and a novel in exploring the “unspeakables” will bring novelty to Nyathi’s and other literary works.